Development of bitter gourd candy and its Quality evaluation - PARDEEP SINGH,; K.A. ATHMASELVI, (International Journal of Pharma and Bio Sciences, 2018)
Bitter gourd candy was prepared with three different concentration of sugar and litchi crush by using 50% sugar and 50% litchi crush (S1), 70% sugar and 30% litchi crush (S2) and 100% sugar (S3). To establish the best product, the candied product was subjected to 9 point hedonic scale sensory evaluation. The data collected based on sensory evaluation were statistically analyzed at 5% level of significance that shows significant difference (p≤0.05) exists among the products. On the basis of sensory data S2 (70% sugar and 30% litchi crush) candy was found to be most preferable candy as it received the highest score for its colour, flavour, taste, texture and overall acceptability attributes .The freshly prepared candy S2 was analyzed for its chemical composition. Both sensory evaluation and chemical analysis indicated that bitter gourd can also be used for the production of candy like amla candy as a substitution of confectionary which has no nutrition value.